Pengaruh Debt to Equity Ratio terhadap Return on Asset pada PT. Suryo Toto Indonesia Tbk Periode 2010-2019 - Parmuji Parmuji; Irfan Rizka Akbar (Jurnal Neraca Peradaban, 2021)
This study aims to determine the effect of Debt to Equity Ratio on Return on Assets at PT. Suryo Toto Indonesia Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the variable Debt to Equity Ratio obtained an average value of 7.72%. The return on asset variable obtained an average value of 0.62%. Debt to Equity Ratio has a positive and significant effect on Return on Assets with a regression equation value of Y = 2.109 - 0.192X, and a correlation coefficient value of -0.778 or has a strong level of relationship with a determination value of 60.5%. Hypothesis testing obtained a significance of 0.000 <0.05.